Relação entre consciência fonológica e o sucesso na alfabetização: um estudo com crianças alfabetizadas - Macilene Vilma Gonçalves (2009)
This research studies the relationship between phonological awareness and success in investigating the literacy skills of phonological awareness in a group of 12 literate children and with good performance in reading and writing, measured by evaluation on a large scale, Provinha Brasil, which measured the acquisition of alphabetic writing system and the level of literacy for children from the second year of basic education beyond the recognition of the teachers. Differently of other studies that had worked with the prediction, the control and the explicit training in phonological awareness, before the acquisition of reading and writing with subsequent verification of the results, we investigated the presence or absence of phonological awareness skills after the process of acquisition of the reading and the writing. In the research, we verify the level of phonological awareness of the citizens relating this result with the performance in literacy. The results were crossed with some pedagogical aspects involved in the school trajectory of the citizens, such as methods, materials, reports on development and opportunities for training in phonological awareness. As theoretical assumptions were incorporated into studies that showed at least two trends: studies that defend the phonological awareness as predictor of the success in literacy and studies that comprise this interactive, that shows some levels of phonological awareness as essential and others, such as the phonemic awareness, as a result or consequence of learning to read and write. Our results showed, as in previous studies, that some levels of phonological awareness appear to precede the acquisition of written language, but suggested that others, such as phonemic awareness, would be developed after reading and writing, and therefore could not by themselves guarantee only it, or be predictive of success in literacy. From the analysis of the school trajectory of the citizens, our research seems to have raised new possibilities of inquiry in relation to the existence of many other variables that may interfere with the multifaceted phenomenon that is literacy, in addition to phonological awareness.